Evolution of Hot Polaron States with a Nanosecond Lifetime in a Manganite Perovskite. Issue 12 (24th January 2017) - Raiser, Dirk; Mildner, Stephanie; Ifland, Benedikt; Sotoudeh, Mohsen; Blöchl, Peter; Techert, Simone; Jooss, Christian
Abstract : Understanding and controlling the relaxation process of optically excited charge carriers in solids with strong correlations is of great interest in the quest for new strategies to exploit solar energy. Usually, optically excited electrons in a solid thermalize rapidly on a femtosecond to picosecond timescale due to interactions with other electrons and phonons. New mechanisms to slow down thermalization will thus be of great significance for efficient light energy conversion, e.g., in photovoltaic devices. Ultrafast optical pump–probe experiments in the manganite Pr0.65 Ca0.35 MnO3, a photovoltaic, thermoelectric, and electrocatalytic material with strong polaronic correlations, reveal an ultraslow recombination dynamics on a nanosecond‐time scale. The nature of long living excitations is further elucidated by photovoltaic measurements, showing the presence of photodiffusion of excited electron–hole polaron pairs. Theoretical considerations suggest that the excited charge carriers are trapped in a hot polaron state. Escape from this state is possible via a slow dipole‐forbidden recombination process or via rare thermal fluctuations toward a conical intersection followed by a radiation‐less decay. The strong correlation between the excited polaron and the octahedral dynamics of its environment appears to be substantial for stabilizing the hot polaron. Abstract : Ultrafast optical pump –probe experiments in the manganite Pr0.65 Ca0.35 MnO3 reveal a hot polaron state with ultraslow recombination dynamics on a nanosecond time scale in the charge‐ordered phase. This long living excitation gives rise to a pronounced photovoltaic effect in heterojunctions. The strong correlation between excited polarons and cooperative octahedral dynamics appears to be substantial for stabilizing the hot polaron.